1993
DOI: 10.1007/bf00040399
|View full text |Cite
|
Sign up to set email alerts
|

The biotechnology of crop legumes

Abstract: The absence of variety-independent gene transfer methods for major agronomic species has, until now, limited the usefulness of recombinant DNA techniques to crop improvement programs. Until recently, only Solanaceous crops could be used to study fundamental and applied problems in plant sciences. During the past five years rapid advances in cell biology, in combination with the development of novel gene transfer methodology allowed utilization of the tools of plant molecular biology in conventional breeding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Their ability to succeed in the arid or semi-arid habitats is related to nitrogen-demanding metabolism (Sprent and McKey, 1994;Sprent, 2001). Leguminosae family contains some 670 genera (Polhill and Raven, 1981;Polhill 1994), more than 21,000 species (Christou, 1994) and 39 tribes. But, a recent phylogenetic analysis based on intensive molecular studies identified 727 genera, 19,327 species and 36 tribes (Lewis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to succeed in the arid or semi-arid habitats is related to nitrogen-demanding metabolism (Sprent and McKey, 1994;Sprent, 2001). Leguminosae family contains some 670 genera (Polhill and Raven, 1981;Polhill 1994), more than 21,000 species (Christou, 1994) and 39 tribes. But, a recent phylogenetic analysis based on intensive molecular studies identified 727 genera, 19,327 species and 36 tribes (Lewis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Complete cDNA clones encoding some enzymes of each type have been isolated and used to construct transgenic plants overexpressing SODs in the chloroplasts, mitochondria, and cytosol (Bowler et al 1991;Scandalios 1993;Van Camp et al 1996). These studies were performed using model plants for transformation, such as tobacco, but important crop legumes can now be transformed and regenerated with relative ease (Christou 1994). Because legumes are unique amongst crop plants in their ability to fix atmospheric N 2 in symbiosis with rhizobia, transformation of these plants with antioxidant genes could provide additional advantages related to its protective role in nodule activity (Puppo et al 1982;Dalton et al 1998;Matamoros et al 1999).…”
mentioning
confidence: 99%
“…Grain legumes were originally considered to be recalcitrant to genetic manipulation. However, as a result of the recent development of direct DNA transfer technology into organized tissue, it is possible to introduce any foreign gene into most of the grain legumes (Christou, 1994).…”
Section: Use Of Molecular Markersmentioning
confidence: 99%